Pemanfaatan larutan lugol 2% untuk menanggulangi kasus kawin berulang pada sapi di Gampong Cot Madhi, Aceh Besar (Utilization 2% lugols solution to overcome the repeat breeding case of cows in Cot Madhi Village, Aceh Besar) - Syafruddin, S; Adam, Mulyadi; Roslizawaty, R; Siregar, Tongku Nizwan; Hafizuddin, H; Panjaitan, Budianto; Armansyah, Teuku; Wahyuni, Sri; Sayuti, Arman (Buletin Pengabdian, 2021)
The objective of this activity was to introduce the use of Lugol's solution to farmers in Cot Madhi Village as an alternative solution to overcome the repeat breeding case in cows. This activity has involved 10 farmers who have cows suspected of experiencing repeat breeding in the village according to the information from the local inseminator. The implementation of this activity was carried out by two methods, namely (1) education and counseling methods and (2) demonstration and field training methods. From these community service activities that have been carried out, farmers have realized the importance of handling reproductive cases to increase livestock productivity. In addition, participants also understood how to obtain Lugol's solution in the market, did dilution according to the recommended dose, and understood the technical treatment of repeat breeding in cows using Lugol's solution. In conclusion, participants have understood the technical treatment with Lugol's solution.